2000
DOI: 10.3109/07357900009012191
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Pharmacologic Evaluation of Age-Related Toxicity of Adjuvant Chemotherapy in Women with Breast Cancer

Abstract: Despite increasing evidence of benefit from adjuvant chemotherapy, older women with breast cancer are commonly given less aggressive treatment than younger patients. Conflicting prior data regarding age-related toxicity prompted this prospective study. Forty-four women (aged 35-79 years) with early-stage breast cancer were treated with four cycles of adjuvant therapy with doxorubicin 60 mg/m2 i.v. and cyclophosphamide 600 mg/m2 i.v. every 21 days. They were monitored for myelosuppression, cardiotoxicity, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
2
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(83 citation statements)
references
References 25 publications
4
73
2
4
Order By: Relevance
“…A comparable incidence of side effects including myelosuppression, cardiotoxicity, and a decrease in quality of life in relatively healthy women over 65 has recently been reported by Dees, et al using the common adjuvant regimen, doxorubicin and cyclophosphamide. 59 Crivellari, et al 56 have evaluated the toxicity of a standard adjuvant therapy regimen, CMF (cyclophosphamide, methotrexate and fluorouracil), in older patients. Important side effects of CMF including Grade 2 and 3 mucosal toxicity (diarrhea, gastritis, and mucositis) and hematologic toxicity were increased in patients older than 65 years.…”
Section: Chemotherapeutic Options In the Adjuvant Settingmentioning
confidence: 99%
“…A comparable incidence of side effects including myelosuppression, cardiotoxicity, and a decrease in quality of life in relatively healthy women over 65 has recently been reported by Dees, et al using the common adjuvant regimen, doxorubicin and cyclophosphamide. 59 Crivellari, et al 56 have evaluated the toxicity of a standard adjuvant therapy regimen, CMF (cyclophosphamide, methotrexate and fluorouracil), in older patients. Important side effects of CMF including Grade 2 and 3 mucosal toxicity (diarrhea, gastritis, and mucositis) and hematologic toxicity were increased in patients older than 65 years.…”
Section: Chemotherapeutic Options In the Adjuvant Settingmentioning
confidence: 99%
“…The ongoing debate: A number of retrospective studies in various solid tumors have reported that toxicity in general is not increased in the elderly [49][50][51] , although these results have been challenged by other studies [52][53][54] . In elderly patients with advanced HNC in particular, combined data from two phase Ⅲ randomized trials [43] , conducted by the Eastern Cooperative…”
Section: Chemotherapymentioning
confidence: 89%
“…This standard could be debatable according to recent results of randomised trials showing a significant reduction in breast cancer recurrence and mortality with adjuvant chemotherapy for elderly patients (Fargeot et al, 2004;Muss et al, 2005). On the other hand, the advanced age has been found to be an independent prognostic factor of decrease in RDI (Bonadonna et al, 1995;Crivellari et al, 2000;Lyman et al, 2003;Shayne et al, 2006), and to be associated with a higher rate of neutropaenic complications (Crivellari et al, 2000;Dees et al, 2000;Muss et al, 2007), of which clinical consequences were more severe (Balducci and Yates, 2000). Second, the 3 FEC100-3D regimen may be a favourable schedule for re-treatment with a low ANC as docetaxel (D) induces deep but short neutropaenia always corrected on day 22.…”
Section: Discussionmentioning
confidence: 99%